Nilai-nilai Pendidikan Agama Islam dalam Konsep Pendidikan Multikultural - Nur, Muhammad (el Buhuth: Borneo Journal of Islamic Studies, 2019)
Indonesia is a pluralistic country because it has a diversity of cultures (culture), ethnicity (ethnicity), race, religion (religious beliefs). To unite the diversity, the Indonesian nation's motto is written on the symbol of the Indonesian state, Bhinneka Tunggal Ika, with different meanings but still one spirit and also poured into the third Pancasila sila with the sound of Indonesian Unity, of course there are things you want revealed from the diversity that is to know the values in terms of Islamic religious education. To realize this desire the authors use a qualitative descriptive approach. The type of research is library research or library research, namely research conducted by collecting some literature from journals or previous research results as a form of comparison with the research that will be conducted.